Distribution of Metabolic Diseases and Demographic Characteristics of Pilgrims in 2024 Hajj: A Descriptive Cross-sectional Study from the Ministry of Health in Saudi Arabia - Samarkand, Osama (Asian Journal of Pharmaceutics (AJP), 2025)
Religious pilgrimages, such as the Hajj, are well-publicized mass gatherings that attract millions of people worldwide. These events can strain the public health resources of the host nation, requiring a high level of readiness and response capacity. Therefore, this study aims to evaluate the Distribution of metabolic diseases and demographic characteristics of pilgrims in the 2024 Hajj. Materials and Methods: A cross-sectional study was conducted among Hajj pilgrims in Saudi Arabia from June to July 2024. Data were collected using pre-validated questionnaires. The study included pilgrims from diverse backgrounds, both male and female, who were able to complete the questionnaires. The data were analyzed using the Statistical Package for Social Sciences version 27. A Chi-square or Fisher’s exact test was used to determine the association between variables, with a P < 0.05 considered statistically significant. Results: Out of the 4,721 pilgrims who responded, 48.9% were male (n = 2,308) while 51.1% were female. The mean age was 51.74 ± 13.92 years with the most reported metabolic diseases being diabetes, 16.3% followed by obesity, 0.7%. The largest age group was 60 years old (5.4%; n = 253), followed by 50 (4.5%; n = 211) and 55 (4.2%; n = 199) years old. Regarding education, 23.4% had a university degree, while 17.2% were literate. In terms of nationality, 13.1% were from Morocco (n = 617), followed by Yemen (8.7%; n = 409), Iraq (8.6%; n = 405), Indonesia (8.1%; n = 384), Algeria (7.5%; n = 355), Pakistan (6.4%; n = 302), Egypt (6.1%; n = 288), Bangladesh (5.8%; n = 275), and China (5.8%; n = 274). There was a significant difference in gender distribution by nationality (P = 0.001). Conclusion: This study highlights the distribution of pilgrims across nationalities, gender, age, education, and various chronic diseases. The confirmation of the various demographics present during Hajj, the Saudi Arabian leadership to create targeted interventions based on this data to provide adequate facilities.